Faktor-Faktor Yang Berhubungan Dengan Pemberian ASI - feby feby; Selvia Selvia; Fanni Astuti (Jurnal Berita Kesehatan, 2022)
Babies are the main cause of death because of infection diseases which is infection of the respiratory tract and diarrhea.One program in its sent down imr is by mother ( breastfeeding ) while the milk the offspring.Breastfeeding is was the first to infants who give all of vitamin, minerals and the necessary nutrients required by infants to growth in the first six months and there no food or other liquid necessary.One cause of the low the provision of breastfeeding in indonesia is a lack of knowledge of pregnant women, the family and people are going to the importance of breastfeeding.Research aims to understand the factors that associated in any way linkedto the provision of breastfeeding in in the work area of hamlet bonti-bonti mattoanging. village environment.Bantimurung kabupaten.Maros.The kind of research that is used is cross-sectional quantitative analytic with the approach. This research suggests that outcomes of 26 respondents ( mother having a baby < 6 months). There are 16 respondents giving breastfeeding exclusively and 10 respondents did not give. exclusive breastfeeding. Outcomes research shows there is a significant relation between a family of the breastfeeding exclusively to the p <0,05 (0,00). The relationship between health workers to give support breastfeeding is relations with the p <0,05 (0,05). The relationship between breastfeeding is the mother with the relationship with the p & <0,05 (0,00).